2018
DOI: 10.1016/j.healthplace.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Community social capital and inequality in depressive symptoms among older Japanese adults: A multilevel study

Abstract: Although studies have suggested that community social capital contributes to narrow income-based inequality in depression, the impacts may depend on its components. Our multilevel cross-sectional analysis of data from 42,208 men and 45,448 women aged 65 years or older living in 565 school districts in Japan found that higher community-level civic participation (i.e., average levels of group participation in the community) was positively associated with the prevalence of depressive symptoms among the low-income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Place is shown to be linked to PRD [ 49 , 50 , 51 , 52 ], sleep [ 53 ], distress [ 54 , 55 ], stress [ 56 ], suicide [ 57 ], and depression [ 58 ]. SES aspects of the neighborhood, racial composition, physical and social environment, and segregation are all neighborhood and contextual factors that have mental health implications [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Ethnic density is one of the major factors that shapes PRD and depression for minorities including Blacks [ 49 , 54 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Place is shown to be linked to PRD [ 49 , 50 , 51 , 52 ], sleep [ 53 ], distress [ 54 , 55 ], stress [ 56 ], suicide [ 57 ], and depression [ 58 ]. SES aspects of the neighborhood, racial composition, physical and social environment, and segregation are all neighborhood and contextual factors that have mental health implications [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Ethnic density is one of the major factors that shapes PRD and depression for minorities including Blacks [ 49 , 54 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective study designs are useful for establishing a valid relationship between social capital and health 7. Several multilevel prospective studies have suggested contextual effects of social capital on health outcomes, mortality,14 15 self-rated health,16 17 suicide,18 depression19 20 and oral health 21. Although two studies have reported an association between community social capital and the incidence of onset of functional disability among older people,22 23 evidence remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks may decrease with age (Forsman, Herberts, Nyqvist, Wahlbeck & Schierenbeck, 2013) and older people become especially reliant on the capacity of their social connections and community resources in order to maintain a meaningful later life (Cagney & Wen, 2008). Continuing to access a wide range of social networks supports healthy ageing, gives a sense of belonging (Forsman et al, 2013;Litwin & Shiovitz-Ezra, 2010) and can reduce depression symptomology (Haesda, Kondo, Takagi & Kondo, 2018) but inability to access social capital may increase risk of depression (Webber et al, 2011). In later life, poorer health becomes a barrier for some to access adequate social capital (Nyqvist, Cattan, Andersson, Forsman & Gustafson, 2013).…”
Section: Social Capitalmentioning
confidence: 99%
“…Whilst Amber also has access to social support and a cultural network, her agency is compromised by the intensity of her ongoing caring role, which impinges upon her physical and mental health. Even with access to social opportunities, relative impoverishment is associated with finding these social connections less beneficial than for those who have more resources and may even reinforce depressive symptomology (Haesda et al, 2018), or leave the individual feeling like they lack control or excluded from meaningful resources (Moore, Daniel, Gauvin & Dube, 2009).…”
Section: Three: Trajectories Are Shaped By Risk Resources and Agencymentioning
confidence: 99%